2019
DOI: 10.1038/s41598-019-38635-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically consistent derivation of chemical potential of a battery solid particle from the regular solution theory applied to LiFePO4

Abstract: The chemical potential of lithium in LixFePO4 active cathode nanoparticles and the surface free energy between LixFePO4 and electrolyte were determined with the novel thermodynamically consistent application of the regular solution theory. Innovative consideration of crystal anisotropy accounts for the consistent determination of the dependency of the chemical potential on the mechanistically derived enthalpy of mixing and the phase boundary gradient penalty. This enabled the analytic, thermodynamically consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Such a shape of the potential ensures a consistent description of intra-particle phase separation [18] and [21] to [28] as well as inter particle lithium exchange first modeled by Dreyer et al [29].…”
Section: Constitutive Equationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Such a shape of the potential ensures a consistent description of intra-particle phase separation [18] and [21] to [28] as well as inter particle lithium exchange first modeled by Dreyer et al [29].…”
Section: Constitutive Equationsmentioning
confidence: 83%
“…Simulation analysis relies on an advanced continuum Li-ion battery modeling framework [15] featuring sequential multi-scale model linking [16]. This is achieved by thermodynamically consistent upscaling [17] of an advanced and detailed model of LFP particle potential as a function of lithiation determined by a thermodynamically consistent derivation [18]. Another merit of the advanced continuum modelling framework arises from a more consistent reproduction of real multi-particle size distributions and particle connectivity and, therefore, electrode topology on the level of the entire electrode.…”
Section: Simulation Modelmentioning
confidence: 99%
“…26 Another attempt to combine phase-field theory and Battler-Volmer relation was made by Zelič and Katrašnik. 27 They modified the CH equation with introduction of the source term related to the Buttler-Volmer relation. Here, the elastic strain was also taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [15][16][17][19][20][21][22][23][24][25][26][27][28][29] operate with 1-D simulation, thus they are not suitable for analysis of the percolative nature of intercalant transport in interconnected electrode particles and electrolyte forming the network of the diffusion channels characterized by the different values of the species mobility. Also, all the phase-field models of ion intercalation and transport are performed in regular solution approximation, thus they are applicable for molecules with short-range interaction and approximately equal size.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, 6 many types of battery models are shown to simulate multi-physical dynamics of battery (thermal, electrical, mechanical) process and accurately compute battery state. Regarding electrical process simulation, electrochemical 1,7,8 and electrical lumped parameter models 913 are typically used.…”
Section: Introductionmentioning
confidence: 99%